Effects of a Management-Labor Context and Team Play on Ultimatum Game Outcomes. - Arkes, Hal R.; Kagel, John H.; Mezhvinsky, Dimitry (Southern Economic Journal, 2017)
Laboratory experiments are usually done on individuals, but many business decisions involve groups. Therefore, we ran ultimatum games using individuals and two-person teams. We primed business roles with the labels 'labor' and 'management,' or we used the generic labels of 'proposer' and 'responder.' With business labels, individuals offered lower shares at higher stakes with no significant differences in acceptance rates. For teams, business labels had no significant effect on shares offered, with significantly lower acceptance rates at higher stakes. Teams offered less than individuals, along with higher acceptance rates with generic labels, compared to no significant differences with business labels.